Characterisation of malignant and benign musculoskeletal soft tissue lesions using the diffusion weighted magnetic resonance imaging - Latif, Nurulhuda Abdul (2018)
Introduction : Conventional magnetic resonance imaging (MRI) shows some overlapping features of malignant and benign musculoskeletal soft tissue tumour. Objectives : The purpose of this study is to characterise malignant and benign or tumour-like musculoskeletal soft tissue lesions using apparent diffusion coefficients (ADC) and to determine the accuracy of the ADC with histopathological examination (HPE) result. Methodology : Cross sectional study on patients referred for conventional magnetic resonance imaging (MRI) for suspected musculoskeletal soft tissue lesions and fullfilled the inclusion and exclusion criteria. Diffusion weighted imaging (DWI) and ADC maps were evaluated to obtain the mean ADC value. The relationship between the ADC value and type of tumours were analysed with statistical tests. The p value of less than 0.05 was taken as statistically significant. Results : From all the forty (n=40) subjects who came for routine conventional MRI imaging for musculoskeletal lesions, only twenty-three (n=23) subjects full-filled the inclusion and exclusion criteria and histologically proven musculoskeletal soft tissue lesions were included in this study. Thirteen patients (n=13) had histologically proven malignant lesions and ten patients (n=10) had histologically proven benign or tumour-like lesions. Patients with malignant lesions demonstrated lower mean ADC value in comparison with the patient with benign or tumour-like lesions. Based on Mann-Whitney test, the mean ADC was significantly different (p<0.001). The median ADC for malignant lesions was 1.04 x 10- 3 mm2/sec (SD 2.38) and benign lesions was 1.61 x 10-3 mm2/sec (SD 0.51). The sensitivity and specificity of mean ADC in predicting type of musculoskeletal soft tissue lesions comparing to histopathology examination report was 90.1% and 100% respectively with cut off point of 1.3 x 10-3 mm2/sec. Conclusion: There was statistically significant difference of mean ADC value of malignant and benign or tumour-like lesions. DWI was also highly sensitive and specific as compared to tissue analysis to determine type of lesions. Thus, DWI has potential in differentiating malignant and benign soft tissue lesions.